1-MCP application suppresses ethylene biosynthesis and retards fruit softening during cold storage of 'Tegan Blue' Japanese plum - Khan, Ahmad S (Plant science : an international journal of experimental plant biology, 2009)
Copyright © 2009 Elsevier Ireland Ltd. All rights reserved.